Hubungan Self Esteem dengan Self Stigma pada Pasien ODHIV di RSUP Surakarta - Umdhah Mufidhah Wahyu Andini; Widiyono Widiyono; Anik Suwarni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Human Immunodeficiency Virus (HIV) is a virus that weakens the human immune system by infecting white blood cells. People with HIV experience feelings of isolation from their environment due to the disease. Self-confidence is crucial for living life, especially as a person with HIV. Self-esteem is related to the stigma around themselves. This study aims to (1) determine the self-esteem of people with HIV at Surakarta General Hospital (RSUP), (2) determine the self-stigma of people with HIV at RSUP Surakarta, and (3) analyze the correlation between self-esteem and self- stigma in people with HIV at RSUP Surakarta. The subjects of this study were PLHIV patients at RSUP Surakarta. Researchers used a quantitative approach by distributing surveys to 67 respondents. The data analysis technique used the Kendall's Tau test to examine the correlation between variables. The results indicate that the majority of patients have moderate self-esteem and self-stigma. The findings using the Kendall's Tau test indicate a significant correlation between self-esteem and self-stigma in PLHIV patients at RSUP Surakarta. This is due to the fact that the p-value <0.001 (p<0.05) and the correlation coefficient of 0.318. There is a correlation between self-esteem and self-stigma in PLHIV patients at RSUP Surakarta.